2021
DOI: 10.3389/fpsyg.2021.707314
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Teachers’ Stroking Behaviors in EFL Learners’ Active/Passive Motivation and Teacher Success

Abstract: Due to the important role that teachers’ professional success plays in the effectiveness of their students and the education system in which they are involved, the present study investigated whether teacher stroke can predict teacher success through the mediation of students’ active and passive motivation. For this aim, a group of 437 Iranian university English as a Foreign Language (EFL) students were targeted to respond to the teacher success, teacher stroke, and student motivation questionnaires. The main r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 38 publications
0
55
0
1
Order By: Relevance
“…As indicated by previous research, teachers play a significant role in preparing a learning environment that can increase students' academic accomplishments (Dewaele and Dewaele, 2020 ). Accordingly, pre- and in-service teachers should be taught how to create an enjoyable learning environment by showing respect and care toward students, building on positive teacher-student interpersonal relationships (Pishghadam et al, 2021a ), and increasing interest in the target language, which will ultimately aid learners sustain engagement with the L2 learning.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated by previous research, teachers play a significant role in preparing a learning environment that can increase students' academic accomplishments (Dewaele and Dewaele, 2020 ). Accordingly, pre- and in-service teachers should be taught how to create an enjoyable learning environment by showing respect and care toward students, building on positive teacher-student interpersonal relationships (Pishghadam et al, 2021a ), and increasing interest in the target language, which will ultimately aid learners sustain engagement with the L2 learning.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%
“…Except Dewaele and MacIntyre ( 2014 , 2019 ) and Dewaele et al's ( 2019b ) studies which had international samples, there is less empirical evidence on cross-cultural studies, seeking to unravel how individuals from different cultural contexts conceptualize, perceive, and experience positive emotions and characteristics. This is very important because culture is a pivotal factor affecting how our mindset is shaped and reshaped (Pishghadam et al, 2021a ). To fill the identified lacuna in the literature, the authors of the present study and their co-researchers have initiated a new line of cross-cultural studies on positive teacher-, student-, or institution-related variables such as teacher rapport, credibility, care, stroking behaviors (a type of teacher care), work engagement, psychological well-being, students' willingness to attend L2 classes, L2 engagement, loving pedagogy in the Iranian, Polish, British, and Iraqi cultures (e.g., Derakhshan et al, 2021a , b ; Greenier et al, 2021 ; Pishghadam et al, 2021a ).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive teacher-student relationship, motivation, attachment to school, cooperation in class activities, hard work in dealing with problems, friendly help and support, understanding of interpersonal behavior, and creating responsibility and freedom can be effective (Wang et al, 2021). In other words, EFL students who have a warm and intimate relationship with their teachers have high selfconfidence, interest in their teacher, more motivation to learn a positive attitude toward school, and enjoy the acceptance of their peers and classmates (Pishghadam et al, 2021a).…”
Section: Teacher Relatedness and Engagementmentioning
confidence: 99%
“…Teachers are emotionally engaged in their work, and teaching practices carry emotions (Zembylas, 2006). Recent studies have indicated that teachers' emotional behavior, such as stroke and emotioncy, influences students' communicative competence (Pishghadam and Ebrahimi, 2020), learning motivation (Pishghadam et al, 2021a), willingness to attend classes (Pishghadam et al, 2021b), and emotions experienced in classes (Derakhshan et al, 2021). Among the topics related to teacher emotion studies (Wang et al, 2021) is emotional labor.…”
Section: Introductionmentioning
confidence: 99%